Estado y manejo de nuevas plantaciones de cacao injertado en Alto Beni, Bolivia - Bentes Gama, Michelliny; Somarriba, Eduardo; Pinto, Waldo; Pastrana, Angel (CATIE, Turrialba (Costa Rica), 2015)
3 tablas, 15 ref.